DESKRIPSI KESALAHAN SISWA DALAM MENYELESAIKAN SOAL-SOAL HIDROLISIS GARAM DI KELAS XI IPA SMA KATOLIK TALINO - Wilianus Boncel; Eny Enawaty; Rody Putra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2017)
AbstrackThe aims of this examination was to describe student errors when solving problem in salt hydrolysis in XI sains Class SMA Catholic Talino Sungai Ambawang and to explain cause of the errors. This examination is use description method with study case. The subject is student in XI sains class. Instrument to collect the data is question test and interview.  The question test is use essay test. The result of this examination is show us that student errors in esenstial concept (65,29%), errors in comprehend contact between concept (53,54%) and error in comprehend when using concept to solve problems (58,68%). The reason of that errors have two factors that is internal and eksternal factor.Keyword: Description, Errors, Salt Hydrolisis.